A Decreasing Mechanism of the Removal Rate in Wafer Polishing Process - NISHIGUCHI, Takashi; MASUDA, Masami; SASAKI, Hirotaka; OOKAWA, Tetsuo (Journal of the Japan Society for Precision Engineering, Contributed Papers, 2006)
In the wafer polishing process, the polishing removal rate decreases with the increase of the polishing time. In order to investigate this behavior, polishing pads have been analyzed through microscopic topography, and by means of creep deformation, friction coefficient, and sludge accumulation. The creep deformation was observed in the surface layer of a polishing pad when a cyclic force equivalent to the polishing pressure was loaded. Based on the cyclic loading test, the elastic deformation decreases gradually with the increase of the polishing time after passing a wafer on a polishing pad. This creep behavior resulted to the decrease of the supply of slurry, which is the most important factor of the polishing removal rate. Thus the decreasing behavior of removal rate is verified to correlate strongly with the creep behavior of the polishing pad.